COMPARATIVE INVESTIGATION OF REPRODUCTIVE SPHERE OF SOME OLD VINE SORTS IN CONDITIONS OF ARMENIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
Comparative analysis of female and male gametophyte of some old sorts of vines is presented. It is shown that the macrogametophyte is comparatively stable and is characterized with middle level of normal ovules development with elementsof embryo sac. Analysis of microgametophyte showed its wide variability and as a result more preferable the application of this system in biomonitoring.
Keywords: biomonitoring; female and male gametophyte; old sorts of vines; elements of embryo sac